Preparation of Nanomaterial Modified Electrode and Its Sensing Application - Liu, Dong; Yuan, Baiqing (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on nanomaterials and strategies to fabricate the electrode for electrochemistry-based sensors. Excellent nanomaterials are essential for high-performance electrochemical sensors, while strategies for controllable assembly of nanomaterials on the electrode and the fabrication of sensing devices can be also important. This book covers the preparation of nanomaterials (magnesium phyllosilicate, metal-organic frameworks (MOF), and covalent-organic frameworks (COF), the fabrication of electrodes with unique several attracting properties (e.g., transparency) using carbon nanomaterials or novel nanotechnologies, and applications of electrochemical sensors.